Reflective Study on Financial Statement Quality Capability to Influence Firm Performance: Literature Review - Auliyah, Iriana; Agit, Alamsyah (Advances in Economics & Financial Studies, 2024)
Purpose: The study explores factors affecting financial statement quality in MSMEs and their impact on performance. It investigates how financial literacy, technology, control, and governance enhance MSMEs' financial statements. Research Design and Methodology: The study uses a quantitative method with surveys and questionnaires to collect data from MSME owners and managers. Data includes financial literacy, technology use, internal control, and governance. Statistical analysis examines the relationship between variables and financial statement quality. In-depth interviews provide insights into financial reporting challenges and best practices among SMEs. Findings and Discussion: The study found that MSMEs' financial statements quality affects business performance significantly. Better financial statements quality, influenced by financial literacy, technology use, internal control, and governance, helps SMEs manage finances efficiently, access capital, and make strategic decisions. Training in financial statement preparation and digital tools usage can enhance accounting understanding and financial management efficiency. Quality financial statements improve MSMEs' competitiveness, transparency, accountability, and reputation, supporting overall business performance. Implications: Improving MSMEs' financial statements can enhance business performance. Financial literacy, information system adoption, internal control, and corporate governance benefit MSMEs. Training and mentoring on financial statements and digital tools enhance financial management efficiency. Policies supporting SME financial statement quality are crucial for competitiveness and sustainability.